The Godina Principle in the 21st Century: Free Flap Timing after Isolated Lower Extremity Trauma in a Retrospective National Cohort - Habarth-Morales, Theodore E.; Davis, Harrison D.; Rios-Diaz, Arturo J.; Broach, Robyn B.; Serletti, Joseph M.; Azoury, Saïd C.; Levin, L Scott; Kovach, Stephen J., III; Rhemtulla, Irfan A. (Journal of Reconstructive Microsurgery, 2024)
Background The timing of free flap reconstruction after lower extremity trauma has been a controversial debate since Marko Godina's original 72-hour recommendation. Recent advances in microsurgery warrant an evaluation of the optimal time to reconstruction.Methods The Nationwide Readmission Database (2014–2019) was used to identify patients undergoing free flap reconstruction after lower extremity trauma. Risk-adjusted statistical methods were used to identify optimal time where risk of infectious and microsurgical complications increase and to quantify the risk associated with time delays.Results A total of 1,030 patients undergoing reconstruction were identified. The mean time to flap coverage was 24.3 days. Thirty-three percent were performed within 72 hours, 24% from 72 hours to 10 days, 18% from 10 to 30 days, and 24% after 30 days. Flaps performed after 10 days were associated with increased risk of surgical site infection, osteomyelitis, and other wound complications, compared with those performed within 72 hours. There was no increased risk in the period of 72 hours to 10 days. Revision amputation and microsurgical complications were not increased after 10 days. The predicted optimal cutoff was 9.5 days for microsurgical complications and 14.5 days for infectious complications.Conclusion Advances in microsurgery may be responsible for extending the time in which definitive soft tissue coverage is required for wounds resulting from lower extremity trauma. Although it appears the original 72-hour time window can be safely extended, efforts should be made to refer patients to specialty limb salvage centers in a timely fashion.
Keywords: Godina principle; free flap reconstruction; lower extremity trauma